All systems go for second-ever mission to enter Mercury's orbit. (18th October 2018) - Castelvecchi, Davide
European and Japanese €1.6-billion double probe, BepiColombo, will take seven years to reach the Solar System's innermost planet. European and Japanese BepiColombo double probe will be only the second mission in history to enter the planet's orbit. Illustration of BepiColombo scanning Mercury